The association between childhood trauma and adolescent cyberbullying: chain mediating roles of emotional intelligence and online social anxiety - Cao, Guanghai; Wei, Xinyu; Liu, Juan; Li, Xianyin (Frontiers in Psychiatry, 2023)
[Abstract] Objective: This study explored the impact of childhood trauma on adolescent cyberbullying and the mediating roles of emotional intelligence and online social anxiety between them. Methods: The Childhood Trauma Scale, Emotional Intelligence Scale, and Chinese Brief Version of the Social Media User Social Anxiety Scale and Cyber Bullying Scale were used to assess 1,046 adolescents [boys: 297, girls: 749, average age=15.79 years] from four schools in Shandong Province, China. SPSS 25.0 and AMOS 24.0 were used for statistical analysis. Results: 1) Childhood trauma directly and positively predicted adolescents’ cyberbullying; 2) Emotional intelligence and online social anxiety played partial mediating roles in the relationship between childhood trauma and cyberbullying; 3) Emotional intelligence and online social anxiety played a chain mediating role in the relationship between childhood trauma and cyberbullying. Conclusions: This study reveals the relationship and mediating mechanisms between childhood trauma and cyberbullying. It provides implications for the theory and prevention of cyberbullying. Keywords: childhood trauma, emotional intelligence, online social anxiety, cyberbullying, adolescents